Avaliação com base na sustentabilidade da mediação de conflitos judiciais na comarca de Várzea Alegre/CE - Silva, Magda Costa (2024)
The general objective of this research was to evaluate the public policy of judicial conflict mediation in the district of Várzea Alegre - CE. The specific objectives were: to understand the public policy of conflict mediation through the institutional political, environmental, social and economic dimensions; to analyze how the public policy of conflict mediation provides access to justice or not, from the perspective of users; to verify to what extent the culture of peace is present in decision-making within the scenario of procedural litigation, through observations made in the field, using the law and the references surveyed as a paradigm. The evaluation perspective adopted was <Avaliação com Base na Sustentabilidade= (ABS), based on Chacon an Nascimento (2020). The ABS suggests an institutional evaluation that is adaptable, interdisciplinary, integrative and resistant to the political pressures of power groups. In this sense, we used bibliographical and documentary research, descriptive and explanatory, participant-based, with a qualitative approach. The field research was carried out in the city of Várzea Alegre - CE, between the months of March and December 2023, with the aim of verifying the demands and procedural situations, analyzing the types of disputes to find out if they can be resolved through mediation and if this process is taking place. The subjects were identified through the access to justice project developed at the local charity called Associação Beneficente e Cultural Santa Maria (ABCSM). Interviews were carried out with a random sample of people, totaling seven (7) participants, all of whom had the same chance to take part, observing the characteristics of each group. They were divided into two groups: 3 users and 4 non-users of the policy. The findings point to the need for approaches that are sensitive to socio-economic and cultural nuances, reinforcing the importance of judicial conflict mediation policies that consider the diversity of the population as a fundamental element in their design and implementation. The Várzea Alegre ombudsman's office has had a possible beneficial effect on the population, but the demand requires more attention, from a daily ombudsman's office that has an ombudsman every day, but which for various reasons, starting with the shortage of civil servants, is not possible a priori.